Understanding China: A Dialogue with Philip Huang. (July 2019) - Zhou, Li-An
This article aims at engaging in a constructive dialogue with Philip Huang. We approach China's administrative governance and economy from different perspectives but arrive at similar and complementary characterizations. I argue that what makes any theory about China valuable and valid lies in its ability to penetrate both China's history and its present, link theory and evidence, go beyond left and right, and combine East and West. Since it has been dominated by Western standards, academic research about China should stand firmly on historical reality as well as constructive dialogue with Western doctrines, but with full awareness of their implicit assumptions, some of which are bundled with Western-specific experiences, and their potential conceptual traps when applied to China. As an ambitious goal, we also should seek to generalize the experiences of both East and West.